Understanding Indigenous Land Rights and Dispossession: The Legacy of the Doctrine of Discovery - Chavez, Samantha (The Toro Historical Review, 2024)
The paper titled "Understanding Indigenous Land Rights and Dispossession: The Legacy of the Doctrine of Discovery" explores the historical and contemporary impacts of the Doctrine of Discovery on Indigenous land rights. Rooted in medieval European thought and later adopted by the United States, the Doctrine of Discovery provided legal justification for the acquisition of Indigenous lands and the displacement of Indigenous peoples. The paper discusses the legal frameworks, such as Johnson v. McIntosh, that institutionalized the doctrine, diminishing Indigenous sovereignty and property rights. It highlights the ongoing ramifications of the doctrine, with Indigenous communities facing continued legal and social challenges. The analysis of scholarly interpretations reveals a consistent theme of Indigenous dispossession and marginalization due to the doctrine, despite some historians arguing its effects are overstated. The essay traces the evolution of these scholarly views and examines the enduring influence of the Doctrine of Discovery on Indigenous land rights and sovereignty.